MCT1, MCT4 and CD147 expression and 3-bromopyruvate toxicity in colorectal cancer cells are modulated by the extracellular conditions - Pereira-Vieira, Joana (2019)
Monocarboxylate transporters (MCTs) inhibition leads to disruption in glycolysis, induces cell death and decreases cell invasion, revealing the importance of MCT activity in intracellular pH homeostasis and tumor aggressiveness. 3-Bromopyruvate (3BP) is an anti-tumor agent, whose uptake occurs via MCTs. It was the aim of this work to unravel the importance of extracellular conditions on the regulation of MCTs and in 3BP activity. HCT-15 was found to be the most sensitive cell line, and also the one that presented the highest basal expression of both MCT1 and of its chaperone CD147. Glucose starvation and hypoxia induced an increased resistance to 3BP in HCT-15 cells, in contrast to what happens with an extracellular acidic pH, where no alterations in 3BP cytotoxicity was observed. However, no association with MCT1, MCT4 and CD147 expression was observed, except for glucose starvation, where a decrease in CD147 (but not of MCT1 and MCT4) was detected. These results show that 3BP cytotoxicity might include other factors beyond MCTs. Nevertheless, treatment with short-chain fatty acids (SCFAs) increased the expression of MCT4 and CD147 as well as the sensitivity of HCT-15 cells to 3BP. The overall results suggest that MCTs influence the 3BP effect, although they are not the only players in its mechanism of action.